2018
DOI: 10.1111/jan.13542
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of mobile cooperation intervention on students’ clinical learning outcomes: A randomized controlled trial

Abstract: ClinicalTrials.gov: NCT02635295.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 63 publications
(119 reference statements)
1
27
0
1
Order By: Relevance
“…Previous studies have also shown mentoring by nurse teachers to be important to pedagogical and psychological support (Price et al, 2011) as well as student counseling, all of which facilitate a student's professional and clinical practice development (Luhanga et al, 2008). The recent reduction in nurse teacher participation within the clinical learning environment has been accompanied by the introduction of digital technology as a tool for maintaining communication between nurse teachers and students (Strandell-Laine et al, 2018). Earlier research has shown that innovations in digital technologies have significantly changed higher education teaching and learning (Report of European Commission, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have also shown mentoring by nurse teachers to be important to pedagogical and psychological support (Price et al, 2011) as well as student counseling, all of which facilitate a student's professional and clinical practice development (Luhanga et al, 2008). The recent reduction in nurse teacher participation within the clinical learning environment has been accompanied by the introduction of digital technology as a tool for maintaining communication between nurse teachers and students (Strandell-Laine et al, 2018). Earlier research has shown that innovations in digital technologies have significantly changed higher education teaching and learning (Report of European Commission, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, nurse teachers can keep in contact with students via mobile devices (Mackay and Harding, 2009), versatile digital communication tools (Saarikoski et al, 2013), and/or digital discussion forums (Hulkari and Mahlamäki-Kultanen, 2008). Digital technology solutions are considered to be an important communication channel among nurse teachers (Saarikoski et al, 2013;Strandell-Laine et al, 2018), and earlier reports suggest that innovative technologies could enhance the communication between students and nurse teachers.…”
Section: Introductionmentioning
confidence: 99%
“…According to SCOPUS the Journal of Advanced Nursing published 288 documents (of which we coded 148 reporting primary research) in 2018. Our search identified six (4% of research papers) randomized controlled trials that were included in this review (Chiu et al, ; Daigle, Talbot, & French, ; Sampaio, Araújo, Sequeira, Canut, & Martins, ; Strandell‐Laine et al, ; Wang et al, ; Zhu et al, ). Two trials were registered with clinicaltrials.gov, two with ISRCTN (International Standard Randomised Controlled Trials Number) and one with the Chinese clinical trials registry.…”
Section: Resultsmentioning
confidence: 99%
“…Half of the included studies ( n = 3, 50%) were prospectively registered (Chiu et al, ; Sampaio et al, ; Wang et al, ). Two (33%) were retrospectively registered (Strandell‐Laine et al, ; Zhu et al, ). One study was not registered (we emailed the author to confirm this) (Daigle et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…O desfecho secundário foi a taxa de erro de dosagem da medicação durante a sequência da preparação do fármaco até a injeção do fármaco. A4) incluído para a análise desta revisão teve por objetivo avaliar a eficácia da intervenção de cooperação móvel na melhoria da competência e auto-eficácia dos alunos e da qualidade do ambiente de aprendizagem clínica(STRANDELL-LAINE et al, 2018). = 41).…”
unclassified